Criteria for Identifying the Basic Japanese Artonyms in the English Language: a Corpus-Based Approach - I. V. Kononova; E. Yu. Matsugina (Дискурс, 2025)
Introduction. The article tests the hypothesis about the possibility of recognizing borrowed lexical units as the basic xenonyms of the language on the basis of corpus data. The scientific novelty of the study is determined by the fact that there have been no previous attempts to identify the degree of assimilation of Japanese artonyms in English using corpus analysis methods, including the collocation method. The relevance of the study lies in the development of research tools of interlinguoculturalology, the study of the layer of xenonymic lexicon significant for the English-language description of Japanese culture and the clarification of criteria for classifying a xenonym as a commonly used loan word. Methodology and sources. The research is carried out in line with interlinguoculturology. The analysis of empirical material, which comprises Japanese artonyms retrieved from the Corpus of Contemporary American English (COCA), was conducted using methods of corpus linguistics. Results and discussion. The article identifies the Japanese loanwords with the highest frequency and wide representation in different genres (origami, bonsai, anime, manga, haiku, kabuki, karaoke, kimono, futon, and geisha), highlights collocations that allow tracing semantic derivation and assessing the metaphorical potential of xenonyms. The analysis allowed the authors to confirm the possibility of classifying Japanisms according to their status in the English language and the necessity to exclude the lexical units Noh and ikebana from the basic common borrowings due to low statistical indicators of their frequency and their low genre distribution. Conclusion. The algorithm of corpus analysis of xenonymic lexis proposed in this study helps to draw verified conclusions about the status of borrowings in the English language vocabulary. The paper presents new criteria for the identifying commonly used English-language xenonyms: 1) the degree of distribution across genres and 2) representation in at least one genre of the corpus with a normalized frequency equal to or greater than 0.5 per 1 million words (X ≥ 0.5) and in at least two genres with a normalized frequency equal to or greater than 0.1 per 1 million words (X ≥ 0.1). The prospects of the present study include further detailed examination of Japanese loanwords of other topics, as well as extrapolation of the results to all English xenonyms in order to verify their universality.